HAKIKAT PENDIDIK QUR’ANI PROFESIONAL DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Jamel, Jamel (Jurnal Al-Fatih, 2024)
This research, entitled "The Nature of Professional Quranic Educators in the Perspective of Islamic Educational Philosophy," aims to examine in depth the ideal concept of professional Quranic educators based on the philosophical foundations of Islamic education. This research uses a library research method with a descriptive qualitative approach, namely analyzing various relevant primary and secondary literature, such as classical works of Muslim philosophers, interpretations of the Quran, hadiths, and contemporary studies on the professionalism of educators in Islam. The results of the study indicate that professional Quranic educators are figures who have a unity between spirituality, intellectuality, morality, and social responsibility. From an ontological perspective, educators are seen as inheritors of the prophetic mission, tasked with guiding humanity toward an understanding of Allah SWT. Epistemologically, the sources of knowledge used are derived from revelation and reason, which complement each other. Axiologically, the goal of education is directed toward the formation of a perfect human being with noble character. Professionalism in Islam is not only oriented toward technical competence, but also toward the ethical and spiritual dimensions that animate all educational activities. This study confirms that the essence of professional Qur'anic educators is not merely teachers, but also shapers of Qur'anic character and civilization based on the values ​​of monotheism, honesty, trustworthiness, and compassion. These findings provide a conceptual contribution to the development of an integrative, civilized, and relevant Islamic educational paradigm to the challenges of the modern era without losing its spiritual and moral spirit.